2009
DOI: 10.1002/mds.22702
|View full text |Cite
|
Sign up to set email alerts
|

Severity of neuropsychiatric symptoms and dopamine transporter levels in dementia with Lewy bodies: A 123I‐FP‐CIT SPECT study

Abstract: Neuropsychiatric symptoms are frequent in dementia with Lewy bodies (DLB). Dopamine transporter (DAT) imaging with (123)I-labeled ligand N-delta-(fluoropropyl)-2 beta-carbomethoxy-3beta-(4-iodophenyl)tropene ((123)I-FP-CIT), which reliably measures midbrain dopaminergic dysfunction, has provided important evidence on the neurobiological substrate of some of these symptoms including apathy and depression. However, little is known on DAT levels and other distressing symptoms such as delusions and hallucinations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 34 publications
6
40
1
1
Order By: Relevance
“…We did not confirm the findings of Roselli et al (12), as we found no correlation between low striatal binding and the presence of hallucinations. There are some differences between our study and the study by Roselli et al Primarily, 123 I-FP-CIT binds not only to DAT but also to the serotonin transporter, which also is present in the striatum (13), and this factor is not discussed by Roselli et al (13).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We did not confirm the findings of Roselli et al (12), as we found no correlation between low striatal binding and the presence of hallucinations. There are some differences between our study and the study by Roselli et al Primarily, 123 I-FP-CIT binds not only to DAT but also to the serotonin transporter, which also is present in the striatum (13), and this factor is not discussed by Roselli et al (13).…”
Section: Discussioncontrasting
confidence: 99%
“…Roselli et al showed a high inverse correlation between the degree of hallucinations and striatal function assessed with 123 I-FP-CIT (12). This finding is somewhat contradictory to the literature regarding the pathophysiology for hallucinations in DLB patients.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In particular, in a phase III multicentre study among a large cohort of subjects, McKeith and co-workers determined the effectiveness of FP-CIT SPECT to distinguish DLB from other dementias (principally AD), revealing a sensitivity and specificity of respectively 78% and 90% respectively. So far, there have been published many studies that investigated DLB by dopaminergic SPECT (Colloby et al, 2005;David et al, 2008;Lim et al, 2009;O'brien et al, 2009;Roselli et al, 2009;Walker et al, 2007). All these works consistently show the diagnostic value of dopaminergic SPECT as applied to DLB, through the evaluation of the striatal dopaminergic innervations reduction, also in the distinction from other dementias (Soret et al, 2006).…”
Section: Single Photon Emission Computed Tomography (Spect)mentioning
confidence: 80%
“…Heroin addicts have lower levels of striatal dopamine transporter and more depressive symptoms compared with healthy controls (32,33). A previous study on genome-wide DNA methylation profiling identified that DNA methylation levels were lower in patients with major depressive disorder compared with controls and that the majority of the methylated sites (85.7%) were located on the promoter CpG islands (34).…”
Section: P-value Subgroups ------------------------------------------mentioning
confidence: 99%